Does a truly hippocampal sparing subtype of Alzheimer's disease really exist?. (1st February 2022) - Ferreira, Daniel; Mohanty, Rosaleena; Murray, Melissa E; Nordberg, Agneta K; Kantarci, Kejal; Westman, Eric
Abstract: Background: The field of biological subtypes of Alzheimer's disease (AD) has recently gained attention as a strong driver of precision medicine and future clinical trials. Neuropathology and neuroimaging studies have consistently identified four subtypes: hippocampal sparing AD, typical AD, limbic predominant AD, and minimal atrophy or minimal tau NFT AD. An important and still unresolved question is whether a truly hippocampal sparing subtype of AD can really exist, since it would challenge the widely accepted model of NFT spread. To address this question, we conducted a systematic review of the literature and performed original analyses on tau PET data. Method: Our systematic review included a search on EMBASE, PubMed, and Web of Science databases up to October 2020. Original analyses included implementation of several methods for AD subtyping on tau PET, and utilization of five complementary cut points to identify hippocampal sparing AD cases both in published studies and in data from the Alzheimer's Disease Neuroimaging Initiative (ADNI). Result: In the three reviewed neuropathologic studies, we did not find any individual case with tau NFT in the association cortex while completely sparing the hippocampus (i.e., truly hippocampal sparing cases). In the in vivo tau PET studies, more lenient cut points consistently identified AD patients with tau NFT in the association cortex while completely sparing the hippocampus. Conclusion: Our current data suggests that the hippocampal sparing subtype of AD does exist ante‐mortem, at earlier stages of the disease, but more research is needed to understand its pathogenesis and progression during life. Based on the findings from both in vivo tau PET and neuropathologic studies, we suggest that there are two possible independent pathways of tau spread: (1) a canonical pathway with early involvement of entorhinal cortex with subsequent involvement of limbic regions before eventually affecting multimodal association cortices, and (2) a less common pathway that affects multimodal association cortices with limbic involvement observed at end stages of the disease. As emphasized in the Murray 2011 study, hippocampal sparing relative to greater cortical involvement defines the phenotype.